Dissemination of the Importance of Language Recognition in Early Childhood - Hani Subakti (Jurnal Pengabdian Masyarakat Formosa, 2022)
One of the "skills" currently needed is language skills. The role of language is needed both in mastering communication technology and in interacting directly. The focus of this teaching activity is to increase interest in learning the language of the community around the Karang Anyar Village based on story books and teaching aids. The goal to be achieved is in order to increase interest in learning and improve language skills (soft skills). The results achieved are: 1. People understand more about the importance of learning languages ​​since childhood. 2. Children will become familiar with the use of language. 3. Children will have readiness to enter association with various languages ​​and cultures. Language itself begins to be introduced as early as possible to students before they turn 12 years old. Early childhood is a child in the age range of 2-7 years and is a golden period for developing language skills.